A Framework for Understanding Aid Effectiveness Determinants, Strategies and Tradeoffs. Issue 1 (12th December 2013) - Howes, Stephen
Abstract Prominent reform agendas for aid abound. How do they relate to each other? This article tries to organise the aid reform literature by proposing a general framework for thinking about the determinants of aid effectiveness and strategies for improving the same. It presents three schools of thought on aid effectiveness: the recipient, donor and transaction costs schools. It argues that none of the reform agendas proposed by these schools dominates. Although actual aid reform agendas will combine elements of all three schools, there are in fact important tradeoffs between the recipient and the donor school reform agendas, and between the transaction costs and the donor school reform agendas. Contrary to the clarion calls of prominent aid reform advocates, aid reform in practice is a messy and difficult business.